Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1007/s002469900425
|View full text |Cite
|
Sign up to set email alerts
|

Massive Biatrial Myxomas in a Child

Abstract: Cardiac myxomas are rarely diagnosed in children, and biatrial tumors are an unusual presentation in any age group. An 8-year-old boy with massive biatrial cardiac myxomas, who presented in acute cardiogenic shock with no preceding cardiac symptomatology, is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
2
Order By: Relevance
“…Despite the benign pathological pattern, its growth in a small child heart can make it clinically very aggressive, requiring emergency treatment. To our knowledge, there are only several case studies and pooled case reports describing the clinical, pathologic, echocardiographic characteristics and surgical management of the myxoma in pediatric patients [1][2][3][4][5][6][7][8][9][10]. We have not found large series describing its clinical features, surgical treatment and the prognosis.…”
Section: Introductionmentioning
confidence: 78%
“…Despite the benign pathological pattern, its growth in a small child heart can make it clinically very aggressive, requiring emergency treatment. To our knowledge, there are only several case studies and pooled case reports describing the clinical, pathologic, echocardiographic characteristics and surgical management of the myxoma in pediatric patients [1][2][3][4][5][6][7][8][9][10]. We have not found large series describing its clinical features, surgical treatment and the prognosis.…”
Section: Introductionmentioning
confidence: 78%
“…A review by Peachell in 1998 reported approximately 19 cases of this tumor in the literature at that time 2 . Our review of the English literature revealed ten other entries in the literature since 1998 8–17 . These entries describe a total of ten patients with biatrial myxomas.…”
Section: Review Of Literaturementioning
confidence: 86%
“…2 Our review of the English literature revealed ten other entries in the literature since 1998. [8][9][10][11][12][13][14][15][16][17] These entries describe a total of ten patients with biatrial myxomas. This includes large multiyear retrospective reviews of single-center experiences, with the largest experience at any single institution consisting of one biatrial myxoma (Table 1).…”
Section: Historymentioning
confidence: 99%
“…En adultos no hubo casos de rabdomioma, asociación poco frecuente y en niños hubo un caso con mixoma, lo que también es infrecuente 28,29 .…”
Section: Discussionunclassified
“…Los niños de esta serie tenían preferentemente localización ventricular, ya que el tumor más frecuente en ellos es el rabdomioma y en los adultos fue auricular por ser el mixoma en más frecuente. Pueden además localizarse en el endocardio, miocardio o epicardio y dependiendo de su localización, tamaño y número pueden causar síntomas e incluso muerte 27,29 .…”
Section: Tabla 3 Comparación Serie Infantil Y Adultosunclassified